The Influence of Work Motivation, Compensation, Work Discipline and Work Environment on the Performance of Education Staff Employees - Adiwinata, Novie Nostalgia; Ahmad, Aldi; Susana, Nuryani (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The purpose of this research is to determine the influence of work motivation, compensation, work discipline and work environment on the performance of educational staff. The results of the linear regression test show that the independent variables work motivation, compensation, work environment and work discipline together influence the dependent variable of employee work performance at FEM IPB University Bogor by 39.1% while the remaining 61.9% is influenced by other variables which are not included in this study. Meanwhile, the F test results show that the calculated F value processed using SPSS is 7.256, while the F table value seen from the Table of Values for the F Distribution is 2.63. Thus, it can be said that the Fcount = 7.256 > Ftable = 2.63. This means that the independent variables consisting of work motivation, compensation, work environment and work discipline have a significant effect on employee work performance. The results of the t test (partial) show that two variables, namely compensation and work environment, have a significant effect on employee work performance, two more, namely work motivation and work discipline, do not have a significant effect on employee work performance at FEM IPB University Bogor.